Does Product Market Competition Decrease Employers' Training Investments? – Evidence from German Establishment Panel Data - Katja Görlitz; Joel Stiebale (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Using a large panel data set of German manufacturing establishments, this paper investigates the impact of competition on training incidence as well as on the number of trained workers. According to theory, one would expect a negative relationship between product market competition and firms' incentives to invest in employees' general skills (Gersbach and Schmutzler 2006). In our empirical analysis, product market competition is approximated by various measures of competition such as the Herfindahl Index, the number of firms at the 3-digit industry level and the price cost margin. After controlling for unobserved heterogeneity across industries and establishments, there is no significant effect of competition on training. This result is robust towards different samples, model specifications and estimation techniques.
Keywords: J24; L22; D43; C23; 330; Training; human capital; product market competition; Betriebliche Bildungsarbeit; Bildungsinvestition; Wettbewerb; Verarbeitendes Gewerbe; Marktstruktur; Deutschland